Surgical orthodontic intervention for impacted maxillary permanent central incisors: A case series - Kanistika Jha; Manoj Adhikari (Clinical Case Reports, 2023)
Key Clinical Message Impacted maxillary central incisors represent a relatively infrequent occurrence. This condition significantly impacts the patient's self‐esteem and aesthetic concerns. Effective resolution is achievable through a combined strategy involving surgical exposure, bracket attachment, and subsequent orthodontic extrusion. The Surgical orthodontic approach is the optimal strategy for addressing impacted maxillary central incisors. Abstract Central incisor is rarely impacted teeth often associated with supernumerary teeth. This case series includes three cases of central incisor impaction presented with complaints of missing teeth, unesthetic appearance, and unclear speech. All the cases were managed with surgical exposure followed by traction by orthodontic force, restoring smile aesthetics.